2004
DOI: 10.1186/1471-2407-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of neoadjuvant 5-FU + leucovorin + CPT-11 in patients with resectable liver metastases from colorectal adenocarcinoma

Abstract: Background: Following resection of liver metastases from colorectal cancer, 5-year survivals are reportedly 30 -39%. It can be assumed that this clinical situation represents systemic disease. Therefore, it is postulated that systemic chemotherapy would improve outcomes, particularly in those whose disease is sensitive to the agents administered. One potential advantage of neoadjuvant chemotherapy is that it provides in vivo chemosensitivity data. Response to neoadjuvant chemotherapy could therefore guide adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…Nowadays, it can be useful to determine the necessity of intensive follow-up and adjuvant therapy for CRC by predicting recurrence and metastases in curative surgical resection (Bathe et al, 2004;Kornmann et al, 2008;Wolpin and Mayer, 2008). In this study, clinico-pathological analysis revealed that TRIB3 is closely related to metastasis, but not to lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Nowadays, it can be useful to determine the necessity of intensive follow-up and adjuvant therapy for CRC by predicting recurrence and metastases in curative surgical resection (Bathe et al, 2004;Kornmann et al, 2008;Wolpin and Mayer, 2008). In this study, clinico-pathological analysis revealed that TRIB3 is closely related to metastasis, but not to lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…In gastrointestinal cancer therapy, it is essential to prevent metachronous metastasis. Several adjuvant chemotherapies are helpful in certain disease stages, especially in CRC (Bathe et al, 2004;Andre et al, 2007). Recently, increasing evidence has been accumulated, showing the usefulness of less invasive surgery in the treatment of CRC, such as laparoscopic and endoscopic surgery (Lacy et al, 2002;Weeks et al, 2002;Clinical Outcomes of Surgical Therapy Study Group, 2004;Jayne et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…8,12 As such, models to predict the prognosis after curative surgical resection would be useful to determine the necessity of intensive follow-up to select adjuvant therapy. Although the choice of adjuvant chemotherapies was excluded from the analyses of the present study due to multicollinearity in relation to the lymph node metastatic statuses, clinicopathologic analysis revealed that the tumor In this study, they were categorized as M1a according to the TNM classification of UICC.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Patients with localized metastases, such as liver or lung, can achieve long-term survival through curative resection of the metastatic lesions. 8,12 As such, models to predict the prognosis after curative surgical resection would be useful to determine the necessity of intensive follow-up to select adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation